2016
DOI: 10.1590/18069657rbcs20150145
|View full text |Cite
|
Sign up to set email alerts
|

Water-Stable Aggregates and Associated Carbon in a Subtropical Rice Soil Under Variable Tillage

Abstract: Tillage systems can influence C sequestration by changing aggregate formation and C distribution within the aggregate. This study was undertaken to explore the impact of no-tillage without straw (NT-S) and with straw (NT+S), and moldboard plow without straw (MP-S) and with straw (MP+S), on soil aggregation and aggregate-associated C after six years of double rice planting in a Hydragric Anthrosol in Guangxi, southwest of China. Soil samples of 0.00-0.05, 0.05-0.20 and 0.20-0.30 m layers were wet-sieved and div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…Ou et al. (2016) indicated that the conversion from CT to MT increased SOC storage by increasing the formation and stabilization of aggregates, followed by increased physical protection of SOC within aggregates under the double rice systems. Our results with MT agreed with the findings of Jiang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Ou et al. (2016) indicated that the conversion from CT to MT increased SOC storage by increasing the formation and stabilization of aggregates, followed by increased physical protection of SOC within aggregates under the double rice systems. Our results with MT agreed with the findings of Jiang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Soil organic carbon (SOC) is of great importance for soil quality (Plaza-Bonilla et al, 2013;Yang et al, 2014;Yu et al, 2015;Yazdanpanah et al, 2016) and the sustainable development of the environment (Benbi et al, 2016;Ou et al, 2016). It is important to ensure the long-term sustainability of SOC in agro-ecosystems to maintain soil fertility (Liang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Hui-Ping Ou et al, (2016) reported that the average humic and fulvic acids concentrations for all the aggregate size fractions was43.9% higher in NT-S than in MP-S, and 20.5% higher in NT+S than in MP+S in the 0.00-0.05 m layer. However, an opposite trend was observed in the 0.05-0.20 and 0.20-0.30 m layers.…”
Section: Aggregate Size Distributionmentioning
confidence: 99%
“…Moreover, less labile and nonlabile fractions contribute more than 50% of TOC, indicating more recalcitrant form of carbon in the soil. Ou et al, (2016) reported that the tillage systems obviously affected the distribution of soil aggregates with different sizes. The proportion of the >2 mm aggregate fraction in NT+S was 7.1 % higher than that in NT-S in the 0.00-0.05 m layer.…”
Section: Aggregate Size Distributionmentioning
confidence: 99%